Preventive Behaviors, Knowledge of Esophageal Cancer and Relationships Socio-Demographic Characteristics Among Older Adults: A Cross Sectional Study - Bayındır Çevik, Ayfer; Yildiz, Hicran; Sert, Havva; Çevik, Ayfer Bayındır (Sage Publications Inc, 2025)
Purpose: This study aimed to investigate the risks of esophageal cancer (EC), protective behaviors, and risk awareness among Turkish adults aged 50 years and older, as well as their relationships with sociodemographic characteristics. Design: Cross-sectional. Recruitment took place between February-April 2022, via online google forms and WhatsApp. Setting: Participants completed the survey online throught WhatsApp. Sample: Analyses included 214 participants (>= 50 years from three provinces of Turkey); 73.8% female (n:158), 62.6% between 50-60 years (n:134 ), 55.6% had a university education (n:47). Measures: Study-specific survey items included questions about demographics, risky conditions and diseases, preventive health behaviors and Esophageal Cancer Knowledge Test (ECRKT). Analyses: Frequency or Mean, Percentage, Independent Samples t-Test, one-way analysis of variance (ANOVA), post hoc analysis (Tukey, LSD), and Cohen's effect size and linear regression analysis. Results: The participants had low ECRKT scores (x:13.50 +/- 9.33, Min:0, Max:31) and reported the most consumed hot beverages (36.9%) among negative EC preventive behaviors. Male gender, not working, not having previously received training on EC, low education and income status cause low knowledge and awareness about EC (P < 0.05). Most of the participants had oral herpes (54.7%), vitamin deficiency (49.1%), and obesity (47.2%) in the past or now. Regarding the participants' EC risk knowledge and, female gender, being between 50-60 years old, and being employed had a weak effect (eta(2)<0.01), while having previous EC training had a moderate effect (eta(2) = 0.006), and having university or higher education had a large positive effect (eta(2) = 0.14) (P < 0.05). Participants' level of education and previous educational experiences contribute significantly to esophageal cancer risk knowledge (P < 0.01). Conclusion: These findings highlight adults aged >= 50 years are exposed to significant EC risks, and have poor knowledge of EC risks. These results highlight the urgent need for educational campaigns to improve EC awareness.
Keywords: Esophageal Cancer; Protective Behaviors; Esophageal Cancer Risks; Esophageal Cancer Knowledge; And Sociodemographic Characteristics